A Discussion of Supply-side Solutions to Carbon Reduction in the Energy Sector - Zhan Qi (E3S Web of Conferences)
Climate change is evolving into a very concern that has to be taken into account, and the energy sector is observed to be to blame for the excessive emissions of greenhouse gas (GHG), mainly carbon dioxide, among all kinds of human activities. While great efforts are made to cover the gap between carbon emission and absorption through energy consumption, limited attention has been drawn to the supply-side. Therefore, the study aims at exploring supply-side solutions to emission reduction in the energy sector by drawing a blueprint for low-carbon energy supply and providing suggestions for solutions based on the logic behind each strategy. The article divides the supply-side solutions into industrial solutions and auxiliary solutions in accordance with their connection with the energy industry. Further, it discusses sub-types of solutions along economic and technological feasibilities of renewable energy technologies (RETs). The research concludes that the low-carbon transition of energy supply is in urgent need for systematic supply-side solutions. Admittedly, the alignment with the climate goal of carbon reduction is the key component of supply-side solutions; nevertheless, the solutions should go beyond and give consideration to promoting the transition as a whole.